Review of the genus Andrioplecta Obraztsov (Lepidoptera: Tortricidae: Olethreutinae) from China - Lv, Jinmei; Sun, Yinghui; Li, Houhun (Zootaxa, 2014)
The Chinese species of Andrioplecta Obraztsov, 1968 are reviewed. Six species are treated, including one new species (A. angusticuculla, sp. nov.) and three species newly recorded from China (A. phuluangensis, A. shoreae and A. suboxystaura). Images and descriptions of adults and genitalia are provided, along with a key to the species in China.